Measuring Educational Intervention Impacts on Food Security and Nutrition among Rural Farmers in El Salvador: A Mixed Methods Study - Rafael Quijada Landaverde; Amy E. Boren Alpízar; Sarahi Morales; Matt Baker; John Rayfield (Journal of International Agricultural and Extension Education, 2021)
Food insecurity in rural El Salvador has been a long-standing problem. This mixed-methods study explored rural farmers’ perceptions of their food security situation, identified critical food security needs, and examined farmers’ intentions to adopt measures to enhance their food security after an educational intervention to combat food insecurity in the area. For this community, the results reveal that access and utilization are the food security dimensions in which farmers perceive the most significant challenges. To mitigate these challenges, farmers participated in an educational intervention that addressed food and nutrition security issues, including household food production, food safety, and drinking water treatments. Post-intervention results show an increase in farmers' intentions to adopt new food production, processing, and preparation practices that improve household food and nutrition security. However, the results highlight farmers' need for continuing education to fully address all food problems in the community
Keywords: El Salvador; farmers; food security; household nutrition; educational intervention